The effect of cultivar, sowing date and transplant location in field on bolting of Welsh onion (Allium fistulosum L.) - Dong, Yinxin (BMC Plant Biol, 2013)
BACKGROUND: Bolting reduces the quality and commercial yield of Welsh onion (Allium fistulosum L.) in production. However, seed production is directly dependent on flower induction and bolting. The Welsh onion belongs to the green plant vernalisation type, specific seedling characteristics and sufficient accumulated time at low temperature are indispensible for the completion of its vernalisation process. Only if these conditions for vernalisation are fulfilled, the plants will bolt in the following year. The present investigation evaluated the effects of cultivar, sowing date and transplant location in field on the bolting of Welsh onion at the Horticultural Farm of the College of Horticulture, Northwest A&F University, Yangling, Shannxi Province, China in two succeeding production years: 2010–2011 and 2011–2012. A strip split plot layout within a randomised complete block design with three replications was used. RESULTS: The results revealed that all three factors (cultivar, sowing date and transplant location) and their interaction had significant effects on the initiation and final rate of bolting observed by 30 April. The earliest bolting date (14 February, 2011 and 15 February, 2012) and the highest bolting rate (100% in 2011 and 62% in 2012) occurred when the JinGuan cultivar was sown on 20 August and transplanted in a plastic tunnel, whereas the latest date and lowest rate (no bolting observed until 30 April) of bolting occurred when the XiaHei cultivar was sown on 29 September and transplanted in an open field. CONCLUSIONS: These results suggest that we can control bolting in Welsh onion production by choosing an appropriate cultivar, sowing date and transplant location. Choosing a late bolting cultivar, such as cultivar XiaHei, sowing around October, and transplanting in the open field can significantly delay bolting, while a sowing date in late August should be selected for seed production, and the seedlings should be transplanted in a plastic tunnel to accelerate development of the flower buds.